ANALISIS PENERAPAN e-KINERJA DAN SELF-EFFICACY TERHADAP KINERJA KARYAWAN PADA INDUSTRI KREATIF DI JAKARTA INTEGRITAS SEBAGAI MODERASI - Yuliniar, Yuliniar; Hadisaputro, Bimo; Supriadi, Yudi Nur (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
This research was conducted using testing through quantitative methods that aimed to determine the effect of the application of e-performance and self-efficacy on employee performance conducted on Creative Industry Employees in Jakarta. Respondents in this study were 150 employees, with sampling using the slovin approach formula with an error rate of 5%. The analysis technique used is the path analysis method and data processing is carried out through SmartPLS 3.0. The results of testing this study are obtained (1) e-performance has a positive and significant effect on performance, (2) Self-efficacy has a positive and significant effect on performance